The guidelines for content creators creating a competitive advantage over online media industry - Jakkrin Kaopattanaskul; Sunee Wattanakomol; Thanin Silpcharu (Decision Science Letters)
This study aimed to develop strategic guidelines for content creators to achieve a competitive advantage in the online media industry by constructing a structural equation model (SEM). A mixed-methods approach was used, combining qualitative interviews with nine industry experts, a focus group with eleven specialists, and a quantitative survey of 500 executives from industrial businesses. Data were analyzed using descriptive statistics, inferential tests, and multivariate techniques. The analysis identified four key strategic components: (1) cost effectiveness, (2) data-driven, (3) differentiated creation, and (4) agile marketing. Cost effectiveness emerged as the most critical factor. Hypothesis testing indicated that business duration significantly influenced the prioritization of these components (p < 0.05). The refined SEM demonstrated strong model fit, with CMIN–p = 0.062, CMIN/DF = 1.142, GFI = 0.955, and RMSEA = 0.0173. The findings confirm the model’s applicability in supporting strategic planning and enhancing competitiveness among online content creator businesses.